The Rural Electrification Agency of Nigeria and Power Supply in Kogi State, Nigeria: An Empirical Analysis - Onoja, Precious EleOjo; Achimugu, Hassan (Pelopor Publikasi Akademika, 2025)
Nigeria faces a significant energy access deficit, with rural communities disproportionately affected by unreliable or non-existent electricity supply. In response, the Rural Electrification Agency (REA) was established to bridge the power access gap through initiatives such as solar Mini-Grids and standalone home systems. This study investigates the impact of REA’s interventions in four rural communities in Kogi East; Ikem Ogugu, Ugbedomagwu, Ejule, Ala, and Agojeju-Odo; between 2015 and 2025. The research evaluates the extent to which these interventions have improved electricity access, reliability, and quality, while also examining the challenges hindering project effectiveness. Employing both quantitative and qualitative methods, the findings reveal a moderate but uneven improvement in electricity delivery and socio-economic conditions across the communities. Specifically, the study provided recommendations such as strengthen community involvement in implementation and maintenance, expand beyond residential connections to productive uses, improve energy reliability through hybrid systems and maintenance support, enhance security infrastructure alongside electrification projects, institute performance monitoring systems for rural electrification projects, prioritize policy alignment and decentralized planning.